PENGARUH KEBIJAKAN MODAL KERJA TERHADAP RETURN ON INVESTMENT PADA INDUSTRI SEMEN DI BURSA EFEK INDONESIA PERIOD[ 2003-2010 - R. Adisetiawan (Universitas Batanghari Jambi, 2011)
This research aim to know do policy of working capital have an effect on to Return On Investment (ROI) at Cement Industry which listed in Indonesia Stock Exchange. Etmten in popullation cement Emiten the taken amount to 3 (three) emiten the cement industry listed in Indonesia Stock Exchange wtth period of research between of 2003 up to year of 20!0. Analysis method the used is Multiple Linear Regression.The data used in this research from the documenation study on Indonesian Capital MarketDirectory and www.1sx,co id Research design model ts nssociatif design, in this case associatif design the used is causal associatif that is existence of causality between one vanehle with other vanabte. This research is cencus type where all populatJons in the cement industry listed in Indonesia Stock Exchangefrom 2003 until 20!0 (during 8 year). The variable used in this research consist of current ratio (X1), working capita! turnover ratio (X2), current assets to total assets (X3), current liabihties to total assets ratio (Xi) is while dependen varible is return on mvestment (Y). Method analysis used is Mulllple Linear Regression Analysis The result indicate that from some working capital policy as of current ratio, work.mg capital turnover ratio, current essers'to total assets and current liabilities to total assetsratio simu!tanly there are the influence significant to the profitability represented by Return on Investment. Partially show only vanabte current ratio and work.mg capital turnover ratio with explamed by variation the expressed in Adjusted R Square equal to 79 percent is while the rest equal to 21 percent influenced by other variable which is not e:-.p!mned by this research model. Research result pursuant to hypothesis test indicate that between some element policy of the working capital is most dominant inOuence the Return on Investment al the cement industry of listed in Indonesia Stock Exchange is current assets to total assets ratio. There by for finance manager and investor have to can and listen carefully to see changes that happened in company especially concerning management of the working capital started from planning, compilation, execution and observation of itself working capital as well as for investor in domg decision ofmvesment require to consider the factor· working capital factor. Keyword: working capital, current ratio, return on mvemncnt, working capital turnover.